2018
DOI: 10.1108/jpbm-10-2017-1610
|View full text |Cite
|
Sign up to set email alerts
|

I’ll have the usual: how restaurant brand image, loyalty, and satisfaction keep customers coming back

Abstract: Purpose The purpose of this paper is to study how repeat customers utilize their established overall restaurant brand image (ORBI), overall restaurant loyalty, satisfaction and behavioral intentions (revisit, recommend) to reengage with a casual-dining restaurant brand. Design/methodology/approach The study design consists of a mixed-methods, two-phase research approach that includes both qualitative and quantitative data. First, focus groups and in-depth interviews with adult customers reveal preliminary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
3
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 76 publications
7
39
3
5
Order By: Relevance
“…Furthermore, Table 6 also explains that the higher the brand image, the higher the brand loyalty would be. However, it is not in accordance with the research results by (Alkhawaldeh and Eneizan, 2018); (Espinosa et al, 2018); (Kim et al, 2018); (Lee et al, 2017); (Lin et al, 2017); and (Liu et al, 2019); (Semadi and Ariyanti, 2018). An increasing or decreasing brand image had no direct impact on brand loyalty.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, Table 6 also explains that the higher the brand image, the higher the brand loyalty would be. However, it is not in accordance with the research results by (Alkhawaldeh and Eneizan, 2018); (Espinosa et al, 2018); (Kim et al, 2018); (Lee et al, 2017); (Lin et al, 2017); and (Liu et al, 2019); (Semadi and Ariyanti, 2018). An increasing or decreasing brand image had no direct impact on brand loyalty.…”
Section: Discussionmentioning
confidence: 54%
“…This is evident from the results of researches by (Iskandar and Berlianto, 2018), (Chinomona, 2016); (Lee and Jee, 2016); (Liu et al, 2019) which confirmed that brand image could contribute to increasing the customer trust in product brands. Besides, previous researches found that the brand image also had positive effects on brand loyalty (Alkhawaldeh and Eneizan, 2018;Espinosa et al, 2018;Kim et al, 2018;Lee et al, 2017;Lin et al, 2017;Liu et al, 2019;Semadi and Ariyanti, 2018;Tran et al, 2019). Therefore, hypotheses that can be formulated are as follows: H4: The higher the brand image, the higher the brand trust.…”
Section: H3mentioning
confidence: 95%
“…Organizations having a positive image are usually get preference among the customers, and it is true, particularly for retailers (Nguyen & Leblanc, 2001). In their study, Espinosa, Ortinau, Krey, and Monahan (2018) argued that restaurant visit (loyalty) is significantly geared up with the presence of positive overall restaurant brand image. Corporate social responsibility helps the firms to develop a positive image which eventually enhances the customer loyalty (Lu, Liu, & Rahman, 2017).…”
Section: Development Of Hypotheses and Conceptual Modelmentioning
confidence: 99%
“…Meanwhile, in the opinion of Espinosa et al (2018), brand image is considered the most important strategy to encourage customers to continue buying products predicted by a company. The study conducted by Johansson et al (2018) suggests that a brand image can be conceptualized as a consumer's perception of a brand that is formed in the minds of the consumers.…”
Section: Introductionmentioning
confidence: 99%